Peer Support and Psychosocial Pain Management Strategies for Children with Systemic Lupus Erythematosus - Laura Nabors; Teminijesu John Ige; Bradley Fevrier (Journal of Immunology Research)
This paper reviews information on Systemic Lupus Erythematosus (SLE) in children. Children with this chronic illness often experience pain related to their condition. They also can experience social isolation. This paper reviews psychosocial information on peer support and cognitive behavioral pain management strategies. The information presented in this paper provides new insights for health professionals assisting children and families in coping with psychological facets of this disease. Research focusing on ways by which peers and friends can support the child’s use of psychological pain management strategies will provide new information for the literature.